Role of Efflux in Antibiotic Resistance of Achromobacter xylosoxidans and Achromobacter insuavis Isolates From Patients With Cystic Fibrosis - Chalhoub, Hussein; Kampmeier, Stefanie; Kahl, Barbara C.; Van Bambeke, Françoise (Frontiers in Microbiology, 2022)
Achromobacter genus (including A. xylosoxidans, the most prevalent Achromobacter species in patients with cystic fibrosis), is poorly susceptible to most conventional antibiotics. Contribution of efflux by AxyABM, AxyXY-OprZ, and AxyEF-OprN and of target mutations were studied in clinical isolates of A. xylosoxidans and A. insuavis. Forty-one isolates longitudinally collected from 21 patients with CF were studied by whole genome sequencing (WGS)-typing, determination of MICs of β-lactams, aminoglycosides, colistin, azithromycin, ciprofloxacin, chloramphenicol, and doxycycline, and expression (quantitative RT-PCR) and function (measure of the uptake of a fluorescent substrate) of efflux pumps. WGS-based typing resulted in 10 clusters comprising 2 or 3 isolates and 20 singletons. The efflux activity was high in strains with elevated MICs for amikacin or azithromycin. This work sheds a new light on the impact of efflux and target mutations in resistance of Achromobacter to several drugs.